Peningkatan Motivasi Belajar melalui Media Pembelajaran Online (Quizizz) pada Mahasiswa Universitas Islam Negeri Raden Fatah Palembang - Oviyanti, Fitri; Ananda, Wiga (Universitas Negeri Padang, 2024)
This study aims to describe the application of game-based online learning media, namely the Quizizz application in increasing student motivation in the Tarbiyah and Teacher Training Faculty of UIN Raden Fatah Palembang. This study uses a qualitative approach with descriptive methods. The research subjects were FITK students who took the Islamic Studies course, totaling 34 people. Collecting data through observation, interviews, and documentation. Data were analyzed using the Miles and Huberman analysis technique which consisted of three steps, namely data reduction, data presentation, and drawing conclusions. The results of the study show that student learning motivation tends to increase with the application of game-based online learning media, namely quizizz.